2020
DOI: 10.4317/jced.55720
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of Stevia and Xylitol chewing gum on salivary Streptococcus mutans count – A pilot study

Abstract: Background Stevia is a natural sweetener which is used as sugar substitute. It has been suggested that stevia may be anticariogenic. However, there is limited research in this regard. Hence, the present study was designed to assess reduction in S. mutans in stevia and xylitol chewing gums. The aim of this study is to evaluate the effectiveness of stevia and xylitol chewing gums on salivary Streptococcus mutans count. Material and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 28 publications
0
14
0
9
Order By: Relevance
“…They reported that stevia is equally effective to Xylitol chewing gum in reducing salivary S. mutans and increasing salivary flow rate and salivary pH. Stevia due to its bitter aftertaste is less accepted in children as compared to Xylitol 29,30 .…”
Section: Effect Of Stevia On Dental Healthmentioning
confidence: 99%
“…They reported that stevia is equally effective to Xylitol chewing gum in reducing salivary S. mutans and increasing salivary flow rate and salivary pH. Stevia due to its bitter aftertaste is less accepted in children as compared to Xylitol 29,30 .…”
Section: Effect Of Stevia On Dental Healthmentioning
confidence: 99%
“…Además, reportan que la Stevia en diversas concentraciones aumenta el pH y disminuye la producción del ácido en el Streptococcus mutans (14) . Como también la reducción del recuento salival del Streptococcus mutans, y además aumenta el flujo lo cual evitara que se adhiera la bacteria y el aumento del pH salival para así lograr un efecto anticariogénico (5)(6)(7)15) . Por consiguiente, coincide con nuestra investigación que disminuye el factor de riesgo cariogénico del Streptococcus mutans (16) .…”
Section: Resultsunclassified
“…En las hojas los principales constituyentes fitoquímicos son los Esteviosídeos, Dulcosido A, Steviol, Rebaudiosidos A, B (dulcosido B, C, D, E, F), Steviolbiosida (2) . Las hojas de Stevia procesadas en polvo de color blanco cristalino que lo denominaron Esteviosídeo que es un esteroide glucósido, un ácido diterpenoica esterificado a una unidad de glucosa y combinado en enlace glucosídico a otras dos unidades de glucosa (3,4) , son considerados que puede prevenir las lesiones cariosas porque tiene la habilidad para inhibir el incremento y reproducción de las bacterias bucales y además no metabolizados por el Streptoccocus mutans (5,6) . Se debe impulsar el uso de los edulcorantes para incentivar la búsqueda de nuevas sustancias que no produzcan subproductos como el ácido láctico por el Streptococcus mutans.…”
Section: Introductionunclassified
“…Dental caries is considered one of the commonest oral diseases, which are usually induced through the metabolic activity of the microbial plaque through reducing pH of saliva (1,2) . Tooth caries occur when the hard tooth tissues are softened by the process of demineralization caused by the action of cariogenic bacteria on foods debris especially polysaccharides (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Chewing gum considered a commonly practiced habit that could stimulate the saliva and increases the salivary flow rate (SFR) and it is also could act as the delivering vehicle for therapeutic agents (2) . However, chewing sweetened gum could involve the incidence of the carious process (8) .…”
Section: Introductionmentioning
confidence: 99%